Impact of in ovo and water supplementation of a postbiotic on intestinal integrity and immune responses in broiler chickens challenged with necrotic enteritis - Dong, Bingqi; Calik, Ali; Dalloul, Rami A. (Frontiers in Veterinary Science, 2025)
Necrotic enteritis (NE) is an enterotoxemic disease of poultry caused by Clostridium perfringens and inflicts substantial economic losses in the poultry industry. Postbiotics have emerged as a promising mitigation approach for NE as they can improve birds’ performance and nutrient absorption and reduce NE-associated pathology. This study evaluated the effects of in ovo and post-hatch application of a postbiotic on intestinal health and the response of broilers during a subclinical NE challenge. On embryonic day (d) 18, fertile broiler eggs were injected with 0.2 mL of either water or a postbiotic into the amnion. Male hatchlings (n = 288) were randomly assigned to one of four groups (six replicate cages, 12 birds/cage): (1) NC (in ovo water, no challenge), (2) PIW (postbiotic in ovo and in drinking water, no challenge), (3) NC+ (NC with NE challenge), and (4) PIW+ (PIW with NE challenge). On d 14, all birds in the NE-challenged groups were orally gavaged with 3,000 E. maxima sporulated oocysts, followed by two doses of ~1 × 108 CFU/mL per bird of C. perfringens on d 19 and d 20. Intestinal permeability, jejunum and ileum histomorphology, and mRNA abundance of genes related to gut health and immune response in the jejunum, ileum, and cecal tonsils (CT) were assessed. Data were analyzed using Student’s t-test and two-way ANOVA, with significance set at a p-value ≤ 0.05. On d 14, the PIW birds exhibited reduced crypt depth (CD) and an increased villus height-to-crypt depth (VH: CD) ratio in the jejunum. In addition, mRNA abundance of mucin-2 and olfactomedin-4 was higher in the PIW birds, while the levels of tumor necrosis factor alpha (TNF-α), inducible nitric oxide synthase (iNOS), interferon gamma (IFN-γ), and interleukin-10 were lower compared to the NC group. On d 21, intestinal permeability was not significantly affected, while postbiotic supplementation resulted in better villi and crypt structures, as manifested by a higher VH: CD ratio. Furthermore, the NE-challenged birds with postbiotic supplementation had higher mRNA abundance of zonula occludens-1 (ZO-1) and TNF-α in the jejunum and iNOS in the CT compared to the NE-challenged control group. In conclusion, supplementation of a postbiotic in ovo and via drinking water demonstrates potential to improve intestinal health and regulate immune responses during a subclinical NE challenge.